1987
DOI: 10.1007/bf01945539
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a hexaprenylhydroquinone sulfate from the marine spongeDysidea sp. as an H, K-ATPase inhibitor

Abstract: A hexaprenylhydroquinone sulfate has been isolated as an H,K-ATPase inhibitor from a marine sponge Dysidea sp. It also inhibited phospholipase A2 as well as secretion of gastric acid in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…Biological studies conducted on several polyprenylhydroquinones showed them to have a moderate antibacterial [11,12], antiviral [13], anti-inflammatory [14,15], and phospholipase A2 activity [15]. These linear polyprenylhydroquinones could be further divided in two main groups with polyprenylhydroquinones sulfates [1620] and hydroxylated polyprenylhydroquinones. To date only four hydroxylated polyprenylhydroquinones [5,6,20,21] have been isolated from Sarcotragus spinosulus (under the name Ircinia spinosula ).…”
Section: Introductionmentioning
confidence: 99%
“…Biological studies conducted on several polyprenylhydroquinones showed them to have a moderate antibacterial [11,12], antiviral [13], anti-inflammatory [14,15], and phospholipase A2 activity [15]. These linear polyprenylhydroquinones could be further divided in two main groups with polyprenylhydroquinones sulfates [1620] and hydroxylated polyprenylhydroquinones. To date only four hydroxylated polyprenylhydroquinones [5,6,20,21] have been isolated from Sarcotragus spinosulus (under the name Ircinia spinosula ).…”
Section: Introductionmentioning
confidence: 99%
“…ircisulfamide) and glycosphingolipids (ircicerebroside) have been isolated from I. fasciculata . Fusetani and colleagues 5 isolated hexaprenylhydroquinone sulfate from a marine sponge Dysidea sp. and reported inhibitory activities on K‐ATPase and phospholipase A2.…”
Section: Introductionmentioning
confidence: 99%
“…Their structures have been established by spectral methods and chemical transformations.In the course of our search for bioactive metabolites from Indian marine invertebrates (1-3), we investigated the sponge Ircinia fasciculata Pallas (Spongillidae) collected on the coast of the Gulf of Mannar, India. In previous reports the genus Ircinia has been shown to produce fiiranosesterterpenes (4-6) and polyprenylated hydroquinones (7-8) [1][2][3][4].Recently, sulfated derivatives of polyprenylated hydroquinones [5, [7][8][9] and the chromenols 11-13 have been isolated from a Dysidea species (9) and Sarcotragus spinulosus (10). These sulfated metabolites have been shown to inhibit H+, K+ and Na+, K+-ATPase.…”
mentioning
confidence: 99%